Identity and Leisure Time: Aspiration of Muslim Influencers on Instagram: Identitas dan Waktu Luang: Aspirasi Influencer Muslim di Instagram - Rezki Putri Nur Aini (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2021)
Abstract This paper analyzes the segmentation of identity and aspirations through the discourse of leisure time carried by Indonesian Muslim influencers as a representation of the negotiation efforts of the Muslim middle class society towards the orientation of religious understanding and popular culture within the framework of modernization. The inevitability of differences in religious understanding among these Muslim influencers ultimately influenced them in representing any discourse carried through new media, including leisure time. The neglected leisure time, its neglected role, is one of the determinants of the new style of Muslim identity when this is deliberately exhibited through various social media platforms. This study is important to see the extent of segmentation due to new identities and aspirations through leisure time that these Muslim influencers want to channel massively on social media, especially Instagram. This study was conduct through netnographic studies supported by various available relevant literature. The results of the study indicate that there are two major segmentation trends among Muslim influencers today through discourse on social media, they are committed Muslim influencers and Muslimist influencers, each of which has different identities and new aspirations in leisure time discourse based on contradiction of mutual religious understanding between them.